Altered frontal cortex functioning in emotion regulation and hopelessness in bipolar disorder. (21st July 2020) - Sankar, Anjali; Purves, Kirstin; Colic, Lejla; Cox Lippard, Elizabeth T.; Millard, Hun; Fan, Siyan; Spencer, Linda; Wang, Fei; Pittman, Brian; Constable, R. Todd; Gross, James J.; Blumberg, Hilary P.
Abstract: Objectives: Emotion regulation difficulties precipitate and exacerbate acute mood symptoms in individuals with bipolar disorder (BD), and contribute to suicidal behavior. However, few studies have examined regional brain responses in explicit emotion regulation during acute BD mood states, or hopelessness, a major suicide risk factor. We assessed brain responses during explicit emotion regulation, and their relationship with hopelessness, in acutely symptomatic and euthymic individuals with BD. Methods: Functional MRI data were obtained from individuals with BD who were either in acute negative (BD‐A; n = 24) or euthymic (BD‐E; n = 24) mood states, and from healthy volunteers (HV; n = 55), while participants performed a paradigm that instructed them to downregulate their responses to fearful (EmReg‐Fear) and happy (EmReg‐Happy) facial stimuli. Emotion regulation‐related differences in brain responses during negative and euthymic BD states, as well as their associations with negative affective symptoms (hopelessness and depression), were examined. Results: Decreased responses were observed in ventral and dorsal frontal regions, including medial orbitofrontal (mOFC) and dorsal anterior cingulate cortices, during EmReg‐Fear across symptomatic and euthymic states in participants with BD relative to HVs. The lowest responses were observed in the BD‐A group. Across BD participants, negative associations were observed between mOFC responses and hopelessness, particularly due to loss of motivation. Differences were not significant during EmReg‐Happy. Conclusions: Lesser emotion regulation‐related ventral and dorsal frontal engagement in BD could represent a trait abnormality that worsens during acute negative states. The reduced mOFC engagement in BD during explicit regulation of negative emotions may contribute to hopelessness particularly in the context of diminished motivation.